INTELITICS: REDEFINIENDO EL SUJETO EDUCATIVO EN LA ERA DE LA INTELIGENCIA ARTIFICIAL - Mili Yaneth Perdomo Prada; Ángela Perdomo Prada (DIALÉCTICA, 2025)
This article examines the profound reconfiguration of educational subjectivities in the era of Artificial Intelligence (AI) and Information and Communication Technologies (ICT). Grounded in Foucault's concept of “technologies of the self,” Castells' theory of the information society, Piscitelli's reflections on digital education, Turkle's analyzes of digital identity, Han's critique of the transparency society, and Jiménez-Agudelo's ideas about “plug and play bodies,” the study explores how these technologies are primarily redefining the nature of learning and the identity of teachers and students. It analyzes how AI and ICT not only transform pedagogical practices, but also radically reconfigure power relations, autonomy and the construction of knowledge in the educational field. The article investigates the implications of this identity metamorphosis, addressing issues such as “algorithmic governmentality”, the emergence of “posthuman intelligences”, and the fusion between the biological and the digital in education. Based on these theoretical frameworks, it is argued that the integration of AI and ICT in education is not a mere adaptation of tools, but rather a paradigmatic change that requires rethinking mainly the concepts of learning, cognition and educational identity. The article proposes a critical approach that, instead of seeking to preserve traditions, ventures into the exploration and configuration of new educational models that respond to the emerging realities of the digital age.